(untitled) (Journal of Social Sciences Review, 2025)
This study aims to explore Begum Nasim Wali Khan’s life, services, political career, and the achievements she made. The political history of Pakistan and the available research establish that hereditary politics is the only source of female political leaders in Pakistan. The main argument of the study is that Begum Nasim Wali Khan is a case in the contrary. Although she had a political background but pursuing and retaining a political position was solely her interest in active politics, adept use of political strategies, and thorough study of Pakistani politics. Begum Nasim Wali Khan demonstrated some rare leadership qualities that won her a prominent place in Pakistan’s political fraternity. Her adept analysis of the political situation assisted her in neutralizing, overcoming, and benefiting from the political crisis. Her political foresight gained her substantial popular support and admiration even from her political competitors. The study proves that she was not just a political figure but also a social activist.